Government measures adopted as a determining factor in business productivity in times of pandemic in latin america and the caribbean. - Lopesierra - Orozco, Jaider Jesús; Redondo - Silvera, Pedro Antonio; Gómez - Mejía, Norberto (Universidad Francisco de Paula Santander, 2023)
Through this article, we seek to generate reflection on the government actions adopted as a determining factor in business productivity in times of pandemic in Latin America and the Caribbean. Given the devastating damage caused by Covid - 19 in the economies of the nations of Latin America and the Caribbean, governments found it necessary to adopt measures to somewhat mitigate the collapse of business, commercial and service productivity. , as a consequence of the sanitary measures implemented, in order to prevent the spread of the virus, which triggered a turbulence to be able to access the products or services due to the restriction and confinement of the population. Which led to a decrease in business productivity to minimal levels. What led to a global crisis caused by the restrictive measures adopted to contain the spread of the coronavirus (Covid-19), is how the governments of the different countries and in order to mitigate the decrease in business productive capacities, adopt public policies aimed at providing financial liquidity to companies and the appropriation of subsidies in order to protect employment, as well as the creation of financial aid and direct aid to the business sector. In other words, the economic, social and public health crisis generated by the coronavirus pandemic exposed a series of weaknesses on the part of the states in terms of having contingency plans that allow them to mitigate and attend to any event or situation in the best possible way. unforeseen event that threatens society and its administrative, economic and production structure.